1977
DOI: 10.3382/ps.0560773
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Electroencephalographic Manifestations of Avian Epilepsy: A Review of the Literature

Abstract: Recently, electrophysiological studies on sleep and wakefulness in birds have yielded useful results. Furthermore, recent evidence obtained in behavioral and electroencephalographical investigations of epileptic birds, induced neuropharmacologically or genetically, have led to recognition of the fact that epileptic seizures are present in aves, and that these seizures reveal many similarities between mammalian and avian epilepsy. While the investigation of birds is of obvrious value for demonstrating the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Those inherited as recessives on the Z chromosome include cerebellar hypoplasia (Winterfield, 1953 ;Markson et al 1959), comatose (Goodwin et al 1950, gasper (Price et al 1966), jittery (Bohren, 1950;Godfrey et al 1953), paroxysm (Cole 1958Kuenzel and Rubenstein, 1974) and shaker (Scott et al 1950;Mueller, 1952). Mutants inherited as recessives on the autosomes include congenital loco (Knowlton, 1929 ;Hutt, 1949), congenital tremor (Hutt and Child, 1934), crazy (McGibbon, 1973), epilepsy (Crawford, 1969;Ookawa, 1977), pirouette (McGibbon, 1974) and tipsy (Hawkes et al 1973).…”
Section: Specific Genes and Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Those inherited as recessives on the Z chromosome include cerebellar hypoplasia (Winterfield, 1953 ;Markson et al 1959), comatose (Goodwin et al 1950, gasper (Price et al 1966), jittery (Bohren, 1950;Godfrey et al 1953), paroxysm (Cole 1958Kuenzel and Rubenstein, 1974) and shaker (Scott et al 1950;Mueller, 1952). Mutants inherited as recessives on the autosomes include congenital loco (Knowlton, 1929 ;Hutt, 1949), congenital tremor (Hutt and Child, 1934), crazy (McGibbon, 1973), epilepsy (Crawford, 1969;Ookawa, 1977), pirouette (McGibbon, 1974) and tipsy (Hawkes et al 1973).…”
Section: Specific Genes and Behavioursmentioning
confidence: 99%
“…This variation may be due to the genetic background of the individual, environmental factors, and a combination of both. Kuenzel and Rubenstein (1974) and Ookawa (1977) examined physiological mechanisms involved with paroxysm and epilepsy, respectively. Deterioration of Purkinjie cells of the cerebellum appears to be associated with shaker (Scott et al 1950) and jittery (Godfrey et al 1953) Overall, however, little is known about the pathways by which behavioural mutants cause phenotypic changes in the fowl.…”
Section: Specific Genes and Behavioursmentioning
confidence: 99%
“…Previous evidence from behavioral and electroencephalographical investigations of birds with seizures (induced pharmacologically or genetically) has led to the recognition that epilepsy is present in avians and that these seizures suggest many similarities between mammalian and avian epilepsies [17]. Recent studies have demonstrated that Gallus gallus have a sudden death syndrome (SDS), characterized by loss of balance, violent flapping, and strong muscular contractions [18].…”
mentioning
confidence: 98%